MENINGKATKAN HASIL BELAJAR MENULIS RESENSIBUKU PENGETAHUAN MELALUI BAKU SIMPUL BERBINTANG SISWA KELAS IX A SEMESTER SATU SMP NEGERI 1WULUHAN - Sudarwati, Ninik (Jurnal Pengembangan Pendidikan, 2013)
Abstrak. Almost a half of students of IX A classwere not able to develop ideas, thoughts, feelings, and information in the formof a review of science book. Most of them were having difficulties in writingsequentially. Students were even had no idea to write. They ended their writingwith two or three sentences as they were afraid of making mistakes and feltdoubtful. They also produced ambigous main ideas. The tacle these problems,“Baku Simpul Berbintang” is applied. It is an acronym for “membaca, diskusi, presentasi,kesimpulan, dan berburu bintang” (reading, discussion, presentation,conclusion, and hunting for stars). The purpose of this study is to developstudents’ learning acheivement of writing science book review through thestrategy used. It is expected that through the used strategy, students are moremotivated, creative, and have high enthusiasm in learning as the strategyemploys enjoyfull activity therefore in the last improving students scores.This study uses Classroom action resarch tmethod of research which is done intwo cycles. In the first cycle it is shown that 58 % percent of the students(21 students) obtain scores of above 77 meanwhile 42% (15 students) obtain lessthan score 77. This result is still considered underachieved so the cycle isrepeated in the second run. In this cycle 90 % of the total students obtainscore 77 and above, and only 10% (4 students) did not obtain the standard. On the basis of this result, the study showsthat there is a significant improvement of students’ learning achievement forboth personal and classical improvement. It can be concluded that “Baku SampulBerbintang” can help to improve students’ skill and competence in writingscience book review. Kata Kunci: menulis resensi, bakusimpul berbintang